Synchronous brain activity in newborn infants and their mothers during parent-led multimodal pain alleviation with skin-to-skin contact, breastfeeding and lullaby singing: Study protocol for a fNIRS hyperscanning study - Mats Eriksson; Majja Lund; Mussie Msghina; Maria Reingardt; Alexandra Ullsten (PLoS ONE, 2026)
Protecting infants’ vulnerable brain during repeated painful procedures like blood-sampling and immunizations in early life is a top priority in neonatal health care. Use of parent-delivered pain management may safeguard the infant brain but at the brain level, it is still unclear what drives the analgesic effect of parent-led interventions such as skin-to-skin contact, breastfeeding, and the parent’s live singing. The objective of this study is to advance our understanding of the neural mechanisms behind parent-led pain management in newborn pain care. Twenty mother-infant dyads will be studied during a planned blood sampling venepuncture, with skin-to-skin contact, breastfeeding, and the mother’s live singing. The potential interbrain synchronous cerebral activation in cortical regions of interest will be registered using functional Near-Infrared Spectroscopy (fNIRS) hyperscanning. Secondly, registration of skin conductance, heart rate variability, and the mother’s gaze will be registered. Social and musical interactions will be studied using microanalysis, as will pain using the Behavioral Indicators of Infant Pain (BIIP). The Swedish Research Ethical Review Authority has approved the study (Dnr 2025-02283-01).